2018
DOI: 10.1111/1748-8583.12215
|View full text |Cite
|
Sign up to set email alerts
|

All of work? All of life? Reconceptualising work‐life balance for the 21st century

Abstract: This paper argues that the study of work‐life balance to date has, in the main, adopted a restricted conception of both “work” and “life”, which does not take account of recent developments in life worlds, working arrangements and employment relationships. “Life” has hitherto been viewed as largely comprising caring activities for dependent children, whereas “work” has been premised largely on a traditional model of work, characterised by full‐time, permanent employment with one employer and a conventional und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
233
1
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(261 citation statements)
references
References 85 publications
3
233
1
24
Order By: Relevance
“…In their review, Chang et al [7] found that the WLB was studied specifically, not in the form of the WFB, in only 9% and 26% of the quantitative and qualitative studies reviewed, respectively. As a result, the knowledge acquired over time about the predictors and consequences of the balance with work is based mainly on the work-family balance [1,10].…”
Section: Specific Nonwork Life Domains: Family and Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…In their review, Chang et al [7] found that the WLB was studied specifically, not in the form of the WFB, in only 9% and 26% of the quantitative and qualitative studies reviewed, respectively. As a result, the knowledge acquired over time about the predictors and consequences of the balance with work is based mainly on the work-family balance [1,10].…”
Section: Specific Nonwork Life Domains: Family and Healthmentioning
confidence: 99%
“…The term work-life balance (WLB) has gained increasing popularity in the public discourse [1]. It is a term that is commonly used in companies, especially large ones, and it is often said to be at the core of their corporate welfare, e.g., [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that the hypothesized relationships may be stronger or weaker under certain conditions. One crucial reason that such practices are used differently among employees is their family responsibilities (Allen, Johnson, Kiburz, & Shockley, 2013;Higgins, Duxbury, & Johnson, 2000;Kelliher, Richardson, & Boiarintseva, 2018;Ortega, 2009;Wood, de Menezes, & Lasaosa, 2003). For example, L. Golden (2009) suggests that married employees and employees with young children make greater use of FWAs, especially for childcare reasons.…”
Section: Family Responsibilitiesmentioning
confidence: 99%